The effect of compression on repetitive behaviors and task participation in children with autism spectrum disorder - Grandits, Jennifer B.; Kent, Hanna W.; Sanborn, Sarah M.; Pilcher, June J. (Frontiers in Psychology, 2023)
Compression clothes are marketed to relieve anxiety and decrease hyperactivity in children with autism. However, few studies have examined the impact of compression for individuals with autism spectrum disorder (ASD). In this study, nine children with autism were observed during Applied Behavioral Analysis therapy sessions while wearing compression clothing. The participants were randomly assigned to wear compression clothing for either their first five sessions or their last five sessions. Videos of the therapy sessions were reviewed and each child's "off task" behavior was identified in the following domains: motor, verbal, and visual. In addition, frequency of the child's repetitive behaviors and external visual stimuli were recorded.The compression clothes failed to increase task participation or reduce the participants' repetitive behavior suggesting that the clothing may not contribute to professional practice of ABA therapy.